Jam! : the story of jazz music - Lee, Jeanne (New York : Rosen, 1999)
Describes the history and development of jazz music in America from its roots in Africa to the contemporary music scene
African tradition -- Africans in America -- Parent of jazz -- New Orleans scene -- Jazz catching fire -- Bebop and beyond -- Looking to the future -- Glossary
Includes discography (p. 59-60), bibliographical references (p. 61), and index
Keywords: Jazz -- History and criticism -- Juvenile literature